2009
DOI: 10.1111/j.1600-051x.2009.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone formation around coated implants

Abstract: Data analysis suggests that collagen/CS has a positive influence on bone formation after 1 month of endosseous healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 17 publications
(28 reference statements)
9
49
1
Order By: Relevance
“…In a further study this was verified for Coll/CS-coated Ti implants compared to controls after 1 month. However, after 2 months no differences could be detected between these groups indicating that Coll/ CS enhances early bone formation [83]. Nevertheless, studies in osteoporotic rats could not show significant differences in peri-implant bone formation of Coll/CScoating in comparison to uncoated Ti pins after 2 and 4 weeks.…”
Section: In Vivo-analysis Of Coll Type I/ Chondroitin Sulfate Coatingscontrasting
confidence: 58%
See 1 more Smart Citation
“…In a further study this was verified for Coll/CS-coated Ti implants compared to controls after 1 month. However, after 2 months no differences could be detected between these groups indicating that Coll/ CS enhances early bone formation [83]. Nevertheless, studies in osteoporotic rats could not show significant differences in peri-implant bone formation of Coll/CScoating in comparison to uncoated Ti pins after 2 and 4 weeks.…”
Section: In Vivo-analysis Of Coll Type I/ Chondroitin Sulfate Coatingscontrasting
confidence: 58%
“…In a sheep experiment under loading conditions in the tibia the extraction torque of external fixation pins was slightly increased when pins were coated with Coll/CS in comparison to uncoated pins [64]. The favorable in vivo results of Coll/CS coatings on Ti pins were also confirmed by further studies examining dental implants [82][83][84]. In a minipig study the Coll/ CS-coating showed significantly increased bone-implant contact compared to uncoated surfaces after 6 weeks of implantation [82].…”
Section: In Vivo-analysis Of Coll Type I/ Chondroitin Sulfate Coatingssupporting
confidence: 52%
“…For dental implants, increases in stability have been reported to begin around the fourth week after placement. 21,26,35 Increases in overall stability can be explained by the new bone formation, which has been reported to begin around dental implants approximately 3 weeks after placement in dogs. 36 Although secondary stability might be expected to increase until complete healing around the MSI has taken place, it leveled off after the fifth week in the present study.…”
Section: Longitudinal Changes Of Msi Stabilitymentioning
confidence: 99%
“…1 Polysaccharides, including glycosaminoglycans have been used for implant surface coating, based on both the direct and indirect adhesion mechanism. [12][13][14][15][16][17][18][19][20][21] The advantage of polysaccharides compared to proteins as nanocoating material is that they stay longer at the coated surface and therefore have a cell attracting effect for a longer time. 14 22 23 Thus, the properties enable polysaccharides to carry signal molecules and support biologically active substances.…”
Section: Introductionmentioning
confidence: 99%